Impact of metabolic syndrome on functional outcomes and complications of surgical treatment of prostate cancer. Issue 8 (12th November 2019) - Morlacco, Alessandro; Dal Moro, Fabrizio; Rangel, Laureano J.; Carlson, Rachel E.; Soligo, Matteo; Karnes, Robert Jeffrey
Abstract: Background: Metabolic syndrome (MetS) has a negative impact on functional recovery and complications after many surgical procedures. Aim: To assess the role of Mets on functional outcomes and complications after radical prostatectomy (RP) for prostate cancer. Patients and Methods: Complete data were collected from 5758 patients, undergoing RP at a single referral centers in a 10‐year period and the presence of MetS before surgery was ascertained in 17.7% of them using a modified version of the IDF‐AHA/NHLBI criteria. Outcomes included 1‐year continence and potency rates, early (≤90 days) and late (>90 days) complications. Results: Postoperative continence (no pads) was significantly less likely in MetS patients (75.4% vs 82.6%, P  < .01), despite no difference in preoperative continence. Erections with or without therapy were reached in 55.8% of non‐MetS and 41.8% of MetS patients ( P  < .01), in this case a significant difference in preoperative function was seen. No differences in early and late complications, except for wound infections (5.8% vs 3.9%, P  < .01) were observed. Conclusions: In the present study RP was safe from the complications standpoint in MetS patients, but the presence of the syndrome was a significant risk factor for post‐RP incontinence and impotence.